2017
DOI: 10.1542/peds.2016-3269
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of National Pediatric Quality Measures

Abstract: Pediatric quality measures are predominated by process measures targeting underuse of health care services. The content represented among these measures is broad, although there remain important gaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
(37 reference statements)
0
24
0
Order By: Relevance
“…The momentum for the pediatric studies on readmissions has been driven predominantly by the concern regarding the loss of reimbursement for "preventable" readmissions as is happening with adult hospitals and the use of readmission rates as a measure of quality of care in most pediatric organizations. 18 The purpose of our study was to assess the relationship between malnutrition in the general pediatric inpatient population and unplanned 7-day readmissions in a retrospective study with a large sample at a children' s hospital. Several medical conditions may covary with malnutrition.…”
mentioning
confidence: 99%
“…The momentum for the pediatric studies on readmissions has been driven predominantly by the concern regarding the loss of reimbursement for "preventable" readmissions as is happening with adult hospitals and the use of readmission rates as a measure of quality of care in most pediatric organizations. 18 The purpose of our study was to assess the relationship between malnutrition in the general pediatric inpatient population and unplanned 7-day readmissions in a retrospective study with a large sample at a children' s hospital. Several medical conditions may covary with malnutrition.…”
mentioning
confidence: 99%
“…As an example, .75% of the currently used quality process measures in pediatrics are used to target the underuse of health care services, such as documenting hydration status in gastroenteritis, obtaining a blood culture in patients with community-acquired pneumonia, and performing hearing testing for patients with otitis media with effusion. 4 The implementation of overuse measures, such as the administration of albuterol and/or steroids in bronchiolitis and appropriate testing for children with pharyngitis, is more challenging than that of underuse measures. Improving the adoption of a recommended test or intervention may be easier to conceptualize, accept, and measure.…”
mentioning
confidence: 99%
“…A recent review of 15 national quality measure sets identified 257 unique measures to evaluate pediatric quality of care. 7 Of these, only one focused on mental health hospitalization. This measure, which was endorsed by the National Quality Forum, determines the percentage of discharges for patients six years of age and older who were hospitalized for mental health diagnoses and who had a follow-up visit with a mental health practitioner within seven and 30 days of hospital discharge.…”
mentioning
confidence: 99%